Cromolyn Sodium differentially regulates human mast cell and mouse leukocyte responses to control allergic inflammation. (April 2022) - Puzzovio, Pier Giorgio; Brüggemann, Thayse R.; Pahima, Hadas; Mankuta, David; Levy, Bruce D.; Levi-Schaffer, Francesca
Abstract: Background: Cromolyn Sodium (CS) has been used in the past as an anti-allergy drug owing to its mast cell (MC) stabilizing properties that impair histamine release. However, additional mechanisms for its clinical actions are likely and might help to identify new roles for MCs and leukocytes in regulating inflammation. Here, using human cord blood-derived MCs (CBMCs), mouse bone marrow-derived MCs (BMMCs) and eosinophils (BMEos), and in vivo mouse models of allergic inflammation (AI), additional actions of CS on MCs were determined. Methods: The in vitro effects of CS on IgE-activated human and mouse MCs were assessed by measuring the levels of pro-inflammatory (tryptase, LTC4, IL-8, CD48) and pro-resolution effectors (IL-10, CD300a, Annexin A1) before and after CS treatment. The in vivo effects of daily CS injections on parameters of inflammation were assessed using mouse models of allergic peritonitis (AP) (Ovalbumin/Alum- or Ovalbumin/ S. aureus enterotoxin B) and allergic airways inflammation (AAI) (house dust mite (HDM)). Results: In vitro, CS did not affect pro-inflammatory effectors but significantly increased the anti-inflammatory/pro-resolution CD300a levels and IL-10 release from IgE-activated CBMCs. BMMCs were not affected by CS. In vivo, CS injections decreased total cell and Eos numbers in the peritoneal cavity in the AP models and bronchoalveolar lavage and lungs in the AAI model. CS reduced EPX release from PAF-activated BMEos in vitro, possibly explaining the in vivo findings. Conclusion: Together, these results demonstrate immunomodulatory actions for CS in AI that are broader than only MC stabilization. Graphical Abstract: ga1